Prehistoric life - Matthews, Rupert; Parker, Steve (New York : Gareth Stevens, 2017)
Provides 100 facts about prehistoric life, including fossils, extinction, and the appearance of human ancestors.
Includes glossary, bibliography and index
Primary
Keywords: Dinosaurs -- Miscellanea -- Juvenile literature; Animals, Fossil -- Miscellanea -- Juvenile literature; Prehistoric peoples -- Juvenile literature; Paleontology -- Juvenile literature; Animals, Fossil -- Juvenile literature